1990
DOI: 10.1128/mcb.10.12.6578
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of YPT1/SEC4-related cDNAs from an epithelial cell line.

Abstract: Molecular analysis of Saccharomyces cerevisiae secretion mutants has led to the identification of two Ras-like GTP-binding proteins, Ypt1p and Sec4p, which are essential for transport along the exocytic route. To study the regulation of membrane traffic in epithelial cells, a set of 11 clones encoding proteins similar to the YPT1/SEC4 products were isolated from an MDCK (Madin-Darby canine kidney) cell cDNA library. Four of these proteins, Rab8, -9, -10, and -11, are novel members of this subfamily of Ras-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
115
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(121 citation statements)
references
References 33 publications
6
115
0
Order By: Relevance
“…A small arrow indicates the trypsin cleavage site of E.coli rab5, as determined by N-terminal sequencing of the band recovered from the gel shown in Figure 3, (Padfield et al, 1992). This peptide was selected as a control, because, when compared with most other monomeric GTP-binding proteins (Chavrier et al, 1990b;Valencia et al, 1991), both rab3 and rab5 contain relatively long N-terminal extensions forming an additional domain (see Figure 6). As shown in Figure 7, fusion was inhibited in our assay by relatively low concentrations of the rab5 N-terminal peptide under conditons where the rab3b N-terminal peptide or a rab2 Cterminal peptide were without effect.…”
Section: Rab5 Associated With Early Endosomal Membranes Is Trypsin-sementioning
confidence: 99%
See 1 more Smart Citation
“…A small arrow indicates the trypsin cleavage site of E.coli rab5, as determined by N-terminal sequencing of the band recovered from the gel shown in Figure 3, (Padfield et al, 1992). This peptide was selected as a control, because, when compared with most other monomeric GTP-binding proteins (Chavrier et al, 1990b;Valencia et al, 1991), both rab3 and rab5 contain relatively long N-terminal extensions forming an additional domain (see Figure 6). As shown in Figure 7, fusion was inhibited in our assay by relatively low concentrations of the rab5 N-terminal peptide under conditons where the rab3b N-terminal peptide or a rab2 Cterminal peptide were without effect.…”
Section: Rab5 Associated With Early Endosomal Membranes Is Trypsin-sementioning
confidence: 99%
“…N-terminal sequence of rab proteins. The N-terminal domains of different rab proteins were aligned according to Chavrier et al (1990b). The sequences of the rab3b and rab5 N-terminal domain peptides are underlined.…”
Section: Rab5 Associated With Early Endosomal Membranes Is Trypsin-sementioning
confidence: 99%
“…However, the precise function of rab proteins in this complex process is not yet understood. We have investigated the subcellular distribution of rabllp [5], which although ubiquitously expressed, has been reported to be more abundant in tissues with a high level of secretion [6]. This observation suggested that rabl lp might play a role in the exocytic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this subgroup of closely related proteins seems to be quite heterogeneous, its members having a cell type specific localization and possibly different functions. For Rab4 two isoforms have been discovered: Rab4a is present on the early endosome and regulate recycling but the localization and the function of Rab4b are not yet known [15][16][17].…”
Section: Introductionmentioning
confidence: 99%